SYSTEM OF DIGITAL TRANSFORMATION OF THE INNOVATION ECOSYSTEM - Сімків, Ліля Євгенівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article is devoted to the actual scientific problem of the theoretical and methodological justification of the system of digital transformation of the innovative ecosystem in the conditions of permanent technological changes. The conceptual foundations of the digital innovation ecosystem as a complex, self-organized system, characterized by networking, adaptability, and the ability for anticipatory development, have been studied. It is substantiated that the digital innovation ecosystem is a complex, dynamic network of interconnected elements that provides anticipatory innovative development through horizontal communications, instant information exchange and the ability to permanently reconfigure internal structures. Its structural elements, including subjects of innovative activity, institutional formations, infrastructural components, information and communication platforms and digital technologies, are defined. The main systemic laws and trends of the digital evolution of innovative ecosystems are revealed, which are manifested through the transformation from hierarchical to network models of organization, the digitalization of innovation processes and the increase in the level of technological uncertainty. A conceptual model of the architecture of the digital innovation ecosystem has been developed, which reflects the system integration of key elements and the mechanisms of their interaction, where digital technologies, artificial intelligence and flexible communication platforms play a key role. The strategic directions of digital transformation have been determined, including the development of digital platforms and hubs, the introduction of artificial intelligence technologies, the formation of digital tools for attracting investments and managing intellectual property. The need for the development of digital competencies and the introduction of blockchain technologies to ensure the transparency of innovation processes is substantiated.